Trace metal distribution for water samples of Ludwig Prandtl cruise LP20160725 - Ole Klein; Tristan Zimmermann; Catharina Petrauskas; Anna Ebeling; Andrea Pieper; Johanna Irrgeher; Daniel Pröfrock (PANGAEA, 2022)
Offshore wind energy is a steadily growing sector contributing to the worldwide energy production. The impact of these offshore constructions on the marine environment, however, remains unclear in many aspects. In fact, little is known about potential emissions from corrosion protection systems such as organic coatings or galvanic anodes composed of Al and Zn alloys, used to protect offshore structures. In order to assess potential chemical emissions from offshore wind farms and their impact on the marine environment water and sediment samples were taken in the surroundings of offshore wind farms of the German Bight between 25.07.2016 and 02.08.2016. The water samples were taken with a PFA-coated metal-free water sampler in pre-cleaned LDPE bottles, filtered over <0.45 μm polycarbonate filters into pre-cleaned LDPE bottles and acidified with nitric acid. The filtrates were then measured for their (trace) metal concentrations with ICP-MS/MS coupled online to a seaFAST preconcentration and matrix removal system.